Discrimination of pregnant women in workplace: A lethal fact that goes unnoticed - Pantoja Rosas, Nilton Edwin (2022)
This article analyzes the case of the discrimination suffered by a pregnant woman in the workplace due to her condition despite that she should be afforded special protection by the State and the authorities in line with a number of national and international laws. Likewise, the reasons for and consequences of this type of discrimination are examined.